Final answer:
The equation for the statement '17 less than h equals 42' is h - 17 = 42, which solves to h = 59 when 17 is added to both sides of the equation.
Step-by-step explanation:
To write the given statement as an equation, you would represent '17 less than h' as 'h - 17'. Since this is equal to 42, the equation can be written as h - 17 = 42.
To solve for h, you would add 17 to both sides of the equation, which gives you h = 42 + 17. Finally, adding those numbers together gives you h = 59.